Copper bis(thiosemicarbazone) complexes modulate P‐glycoprotein expression and function in human brain microvascular endothelial cells. Issue 3 (9th April 2022) - Pyun, Jae; McInnes, Lachlan E.; Donnelly, Paul S.; Mawal, Celeste; Bush, Ashley I.; Short, Jennifer L.; Nicolazzo, Joseph A.
Abstract: P‐glycoprotein (P‐gp) is an efflux transporter at the blood–brain barrier (BBB) that hinders brain access of substrate drugs and clears endogenous molecules such as amyloid beta (Aβ) from the brain. As biometals such as copper (Cu) modulate many neuronal signalling pathways linked to P‐gp regulation, it was hypothesised that the bis(thiosemicarbazone) (BTSC) Cu‐releasing complex, copper II glyoxal bis(4‐methyl‐3‐thiosemicarbazone) (Cu II [GTSM]), would enhance P‐gp expression and function at the BBB, while copper II diacetyl bis(4‐methyl‐3‐thiosemicarbazone) (Cu II [ATSM]), which only releases Cu under hypoxic conditions, would not modulate P‐gp expression. Following treatment with 25–250 nM Cu II (BTSC)s for 8–48 h, expression of P‐gp mRNA and protein in human brain endothelial (hCMEC/D3) cells was assessed by RT‐qPCR and Western blot, respectively. P‐gp function was assessed by measuring accumulation of the fluorescent P‐gp substrate, rhodamine 123 and intracellular Cu levels were quantified by inductively coupled plasma mass spectrometry. Interestingly, Cu II (ATSM) significantly enhanced P‐gp expression and function 2‐fold and 1.3‐fold, respectively, whereas Cu II (GTSM) reduced P‐gp expression 0.5‐fold and function by 200%. As both compounds increased intracellular Cu levels, the effect of different BTSC backbones, independent of Cu, on P‐gp expression was assessed. However, only the Cu‐ATSM complex enhanced P‐gp expression and this was mediated partly through activation (1.4‐fold) of the extracellular signal‐regulated kinase 1 and 2, an outcome that was significantly attenuated in the presence of an inhibitor of the mitogen‐activated protein kinase regulatory pathway. Our findings suggest that Cu II (ATSM) and Cu II (GTSM) have the potential to modulate the expression and function of P‐gp at the BBB to impact brain drug delivery and clearance of Aβ. Abstract : P‐glycoprotein (P‐gp) expressed at the blood–brain barrier (BBB) acts as a gatekeeper regulating the transport of molecules into and out of the brain. Two similar copper complexes, Cu II (ATSM) and Cu II (GTSM), have opposite modulatory effects on the expression and function of this efflux transporter that is responsible for keeping the brain a protected sanctuary as well as to clear unwanted molecules like amyloid beta (Aβ) from the brain. This involves the activation of MAPK signalling and MDR1 promoter regions regulating P‐gp. This has implications for enhancing brain drug delivery and clearance of Aβ in Alzheimer's disease.